Kemampuan Berpikir Kritis Matematis Berdasarkan Kecerdasan Multiple Intelligences - Mujib, Mujib; Mardiyah, Mardiyah (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
Based on the cognitive development of junior high school students began to be able to think formal, able to think high level of mathematical thinking or high level mathematical thinking, and mathematical thinking with low order or low level mathematical thinking). The research method used is descriptive qualitative. Data technique used is test method, questionnaire, observation and interview. Data analysis is done descriptively qualitative. This research looks at mathematical thinking based on students' multiple intelligences. Students are Linguistic Intelligence, Logic-Mathematics and Spatial Intelligence. Each intelligence of multiple intelligences capable of reading the problem well, able to store information, images of different mathematical symbols. Being able to understand what to do, have ideas to math symbols. Students can make mathematical formulas clearly, able to differentiate, equate, integrate, classify between variables analyze, summarize, criticize, predict, compose, build, plan, discover, renew, ner, strengthen, beautify, compose. Students who have the tendency of intelligence Linguistic Intelligence how to translate keywords used word for word more compiled. Logical-Mathematical Intelligence. the methods used in solving mathematical problems are seen more structured results, and Intelligence Intelligences ways used with cultural patterns.